2019
DOI: 10.3126/jnps.v38i2.19917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Knowledge on Obesity Among School Going Adolescents of Kaski, Nepal

Abstract: Introduction: Childhood obesity has now been recognized as a global health problem because of its devastating consequences and prevalence at uncontrollable rate worldwide. The objective of this study was to determine prevalence of obesity and find out the knowledge on obesity among school going adolescents. Material and Methods: This descriptive cross-sectional study was conducted among adolescents of two private schools of Kaski district. Altogether 120 adolescent students were selected using census met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
1
10
1
Order By: Relevance
“…Since we conducted a study in urban settings, therefore, we are unable to comment on the difference on the basis of study settings, either urban or rural strata for food consumption. Another study from Pokhara shows that 75% of adolescents had good knowledge (15). However, in our study findings, 66.5% only had inadequate knowledge about junk foods.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Since we conducted a study in urban settings, therefore, we are unable to comment on the difference on the basis of study settings, either urban or rural strata for food consumption. Another study from Pokhara shows that 75% of adolescents had good knowledge (15). However, in our study findings, 66.5% only had inadequate knowledge about junk foods.…”
Section: Discussioncontrasting
confidence: 70%
“…A recent study from Kaski district depicts 8.1% prevalence of overweight and obesity among adolescents (14). Another study conducted in the Kaski district of Nepal shows that the obesity prevalence among adolescents is 3.3% (15). Risky behaviors such as unusual time of sleeping, tobacco and substance abuse, watching television for a longer time, consuming low dietary foods and fruits, along with insufficient physical activities are found to be more prevalent in the Kaski district, which are leading to more risk of deviating health condition of adolescents (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Raut et al 3.5% male children were overweight and 1.2% were obese; whereas only 2.6% females were overweight, and none were obese 3 . But in some studies a higher prevalence was reported in males as well 2,3,7,14 . Our study also showed a higher prevalence in girls, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…Piryani et al showed that 12.2% of adolescent students in Nepal were overweight 2 . A study assessing the knowledge and prevalence of obesity in adolescent children of Kaski district showed that all children with obesity were between 14 to 16 years age group 14 . Our study is comparable with previous studies as the highest prevalence rates of obesity/overweight were seen in the age group of 16 (4.7% and 9.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Not just the physical illness but also the mental issues are emerging - ------------------------------------------------------------------------------Received on 14-03-2021 Accepted on 24-06-2021 due to unhealthy dietary patterns. These mental issues include unhealthy sleep, anxiety and different mood swings which directly or indirectly affecting physical well-being of children 7 . A study conducted in the Kaski district of Nepal highlighted the issue that prevalence of obesity was increasing with various risky mental issues such as sleep disorder, watching television for long time, verbal abuse, insufficient physical activities, low healthy content in diet etc.…”
Section: Introductionmentioning
confidence: 99%